Modern Ukrainian Grand Narrative: Prospects for Evolution - Dobrolyubska, Yuliya; Prysiazhniuk, Oleksii; Rodian, Maria; Semko, Yana (Տիգրան Մեծ)
The article analyzes the features of the modern Ukrainian narrative. Particular attention is paid to inter-preting the term “grand narrative”. By “grand narrative”, we mean the global intellectual narrative of con-cepts of experience and knowledge, which emerged in the Enlightenment. The paper notes that the grand narrative not only managed to systematize European thinking but has made an intellectual expansion into the whole scientific world. Today, the grand narrative is a rather broad concept, and it means a new meth-od of historiography. The article pays attention to historical research methods: chronological, historical-comparative and retrospective. The work is formed based on the conclusions of the classics of Ukrainian history (M. Hrushevsky) and the grand narratives of modern Ukrainian historians. The results of the study show that in Ukraine, several versions of the grand narrative are formed on different scientific principles: multiethnic, Eurocentrism, Westernization (modernization), and nationalism. We believe that bringing the Ukrainian grand narrative into westernization is undesirable because it significantly limits the heuristic potential. But the national-state concept of narrativism has potential in history, as many Ukrainian “sto-ries” are written under the influence of Soviet stereotypes. Therefore, we believe that today we need to rethink narrativism to find a new Ukrainian grand narrative.
Keywords: History